Analisis Implementasi Integrated Reporting pada PT XL Axiata Tbk berdasarkan IR Framework - Diki Ibrahim; Nisrina Jaesa; Nurul Hasanah; Rahmawati; Holiawati (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2024)
Analysis of Integrated Reporting Implementation at PT XL Axiata Tbk Based on the IR Framework. This research examines the implementation of Integrated Reporting (IR) at PT XL Axiata Tbk, referencing